166 Exploring interactions between traumatic brain injury and cognitive co-morbidity: descriptive case analysis from real-world monitoring. Issue 9 (12th August 2022) - Parkinson, Megan; Curtis, Francesca; Dani, Mel; Fertleman, Michael; Kolanko, Magda; Soreq, Eyal; Barnaghi, Payam; Sharp, David; Li, Lucia; ,
Abstract : Introduction: Traumatic Brain Injury (TBI) is common, and increasing in older adults, in whom functional outcomes can be particularly poor. We studied post-TBI recovery using Minder, a remote home monitor- ing system that records sleep and activity data. Methods: We installed Minder in recently discharged patients >60years with moderate-severe TBI. We present comparative descriptive analyses of early post-discharge recovery for two male patients, cross referencing observed data against verified activities and events. Both have similar socioeconomic back- grounds, non-neurological comorbidity burden and household set-up. One had prior cognitive impair- ment (PAT1), whilst the other did not (PAT2). Results: We present 10 weeks of sleep and activity data. The data from PAT1 revealed extremely regular sleep-wake schedule, which remained stable. There was minimal time out of bed overnight, with corresponding bathroom activity, consistent with self-reported overnight toilet trips. Conversely, PAT2's data revealed highly irregular and fragmented sleep patterns, despite PAT2 reporting good sleep. There were significant periods out of bed overnight with activity detected in rooms throughout the house, con- sistent with carer reports of night-time wandering. A period of increased overnight activity coincided with a sequence of falls, necessitating increases in care. Discussion: Our data suggests important interactions between cognitive comorbidity and injury on function after TBI. Our novel approach provides valuable 'real world' insights into TBI recovery, particularly in those with poor insight, and could also help guide clinical care.